A highly sensitive trap vector system for isolating reporter cells and identification of responsive genes. Issue 1 (24th April 2018) - Ishikawa, Kosuke; Kobayashi, Yuta; Wakabayashi, Yutaro; Watanabe, Shinya; Semba, Kentaro
Abstract: We devised a versatile vector system for efficient isolation of reporter cells responding to a certain condition of interest. This system combines nontoxic GAL4-UAS and piggyBac transposon systems, allowing application to mammalian cells and improved expression of a fluorescent reporter protein for cell sorting. Case studies under conditions of c-MYC gene induction or endoplasmic reticulum (ER) stress with thapsigargin on mouse or human cell lines confirmed easy and efficient isolation of responsive reporter cells. Sequence analyses of the integrated loci of the thapsigargin-responsive clones identified responsive genes including BiP and OSBPL9 . OSBPL9 is a novel ER stress-responsive gene and we confirmed that endogenous mRNA expression of OSBPL9 is upregulated by thapsigargin, and is repressed by IRE1α inhibitors, 4μ8C and toyocamycin, but not significantly by a PERK inhibitor, GSK2656157. These results demonstrate that this approach can be used to discover novel genes regulated by any stimuli without the need for microarray analysis, and that it can concomitantly produce reporter cells without identification of stimuli-responsive promoter/enhancer elements. Therefore, this system has a variety of benefits for basic and clinical research.